C9orf72 and UNC13A are shared risk loci for amyotrophic lateral sclerosis and frontotemporal dementia: A genome‐wide meta‐analysis. Issue 1 (27th June 2014) - Diekstra, Frank P.; Van Deerlin, Vivianna M.; van Swieten, John C.; Al‐Chalabi, Ammar; Ludolph, Albert C.; Weishaupt, Jochen H.; Hardiman, Orla; Landers, John E.; Brown, Robert H.; van Es, Michael A.; Pasterkamp, R. Jeroen; Koppers, Max; et al.
<x xml:space="preserve">Abstract</x> Objective Substantial clinical, pathological, and genetic overlap exists between amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). TDP‐43 inclusions have been found in both ALS and FTD cases (FTD‐TDP). Recently, a repeat expansion in C9orf72 was identified as the causal variant in a proportion of ALS and FTD cases. We sought to identify additional evidence for a common genetic basis for the spectrum of ALS‐FTD. Methods We used published genome‐wide association studies data for 4, 377 ALS patients and 13, 017 controls, and 435 pathology‐proven FTD‐TDP cases and 1, 414 controls for genotype imputation. Data were analyzed in a joint meta‐analysis, by replicating topmost associated hits of one disease in the other, and by using a conservative rank products analysis, allocating equal weight to ALS and FTD‐TDP sample sizes. Results Meta‐analysis identified 19 genome‐wide significant single nucleotide polymorphisms (SNPs) in C9orf72 on chromosome 9p21.2 (lowest p = 2.6 × 10−12) and 1 SNP in UNC13A on chromosome 19p13.11 (p = 1.0 × 10−11) as shared susceptibility loci for ALS and FTD‐TDP. Conditioning on the 9p21.2 genotype increased statistical significance at UNC13A. A third signal, on chromosome 8q24.13 at the SPG8 locus coding for strumpellin (p = 3.91 × 10−7) was replicated in an independent cohort of 4, 056 ALS patients and 3, 958 controls (p = 0.026; combined analysis p = 1.01 × 10−7). Interpretation We identified common genetic variants in C9orf72, but in addition in UNC13A that are shared between ALS and FTD. UNC13A provides a novel link between ALS and FTD‐TDP, and identifies changes in neurotransmitter release and synaptic function as a converging mechanism in the pathogenesis of ALS and FTD‐TDP. Ann Neurol 2014;76:120–133